Standardized method for the detection of antibodies to aquaporin-4 based on a highly sensitive immunofluorescence assay employing recombinant target antigen - Jarius, Sven; Probst, C.; Borowski, K.; Franciotta, D.; Wildemann, Brigitte; Stoecker, W.; Wandinger, K. P. (Journal of the neurological sciences, 2010)
Background - Recently, a highly specific serum autoantibody was discovered in patients with neuromyelitis optica, called NMO-IgG, and aquaporin-4, the most abundant water channel in the CNS, was identified as the target antigen. Several assays for the detection of NMO-IgG/AQP4-Ab have been described. Tests based on recombinant human AQP4 have been repeatedly demonstrated to be more sensitive than the previous gold standard assay, i.e. immunohistochemistry (IHC) on mouse brain tissue. However, the sophisticated techniques applied restrict their availability to few laboratories worldwide. - Objective - To develop an easy-to-use, recombinant immunofluorescence assay (rIFA) suitable for standardized and high-throughput detection of NMO-IgG/AQP4-Ab. - Methods - HEK293 cells seeded on cover glasses were transfected with full-length recombinant human AQP4 at large scale. Cover glasses with the immobilized cells were cut into millimetre-sized fragments and transferred to microscopy slides. 151 serum samples from patients with NMO spectrum disorders (NMOSD) and controls were analysed both in the standard IHC assay and in the newly developed rIFA. - Results - 25/32 (78.1%) patients with clinically definite NMO and 36/51 (70.6%) of total patients with NMOSD were positive for NMO-IgG/AQP4-Ab in the rIFA compared to 65.6% and 58.8%, respectively, in the IHC assay. - Conclusion - The recombinant IFA presented here provides laboratories familiar with indirect immunofluorescence microscopy with a highly sensitive and reproducible diagnostic tool for standardized detection of antibodies to AQP4. This new approach could make AQP4-Ab testing, which is of high clinical relevance, more widely available.
Available online 1 February 2010
Gesehen am 18.07.2023